Cultural Impact on Islamic Matrimonial Beliefs: A Comparison between Pakistan and Qatar - Umaima Usman; Waqar Husain (UIN Maulana Malik Ibrahim Malang, 2022)
People from distinct cultural backgrounds practice Islam. The general impact of culture over religion, including Islam, has been well documented. The current study specifically focused on marriage-related Islamic beliefs and intended to analyze the impact of culture in this regard by comparing Pakistani and Qatari Muslims. The study involved 519 participants from Pakistan and Qatar. A specific questionnaire was designed for the current study in Urdu and Arabic. It comprised 26 items and covered various Islamic matrimonial beliefs. The findings revealed that the marital beliefs of Qatari Muslims were significantly closer to the authentic Islamic beliefs than those of Pakistani Muslims. The current study's findings reflected the impact of indigenous culture on the marriage-related beliefs of Pakistani Muslims. Islam diamalkan oleh orang-orang dari latar belakang budaya yang berbeda. Kesan umum budaya terhadap agama, termasuk Islam, telah didokumentasikan dengan baik. Kajian ini secara khusus memberi tumpuan kepada kepercayaan Islam berkaitan perkawinan dan bertujuan untuk menganalisis kesan budaya dalam hal ini dengan membandingkan Muslim Pakistan dan Qatar. Kajian itu melibatkan 519 peserta dari Pakistan dan Qatar. Suatu angket khusus telah dirancang untuk kajian ini dalam bahasa Urdu dan Arab. Angket tersebut mengandung 26 butir dan merangkum pelbagai kepercayaan perkawinan Islam. Hasil menunjukkan bahwa kepercayaan perkawinan orang Islam Qatar lebih dekat dengan kepercayaan Islam tulen berbanding dengan kepercayaan orang Islam Pakistan. Temuan penelitian ini mencerminkan kesan budaya orang asli terhadap kepercayaan berkaitan perkawinan orang Islam Pakistan.